TARI REJANG SANG HYANG IINAN DI DESA ADAT PUJUNGAN KECAMATAN PUPUAN KABUPATEN TABANAN - Ni Wayan Selina Dewi; I Wayan Gata; I Wayan Kary Arta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The sang hyang iinan rejang dance is one of the sacred dances of Pujungan village and is one of the inheritances passed down from generation to generation that must be carried out. This dance is performed every Pujawali Kapat which is held once a year. The people of Pujungan Village believe that the rejang sang hyang iinan dance has a very deep meaning for the community. Based on this background, there are several problem formulations in this research, including: 1) What is the basis of the rejang sang hyang iinan dance in the Pujungan Traditional Village? 2) What is the process of implementing the sang hyang iinan rejang dance in the Pujungan Traditional Village? 3) What is the meaning and function of the sang hyang iinan rejang dance in Pujungan Village? Several theories that researchers use to study the problem and also provide direction and foundation, namely: 1) Religious Theory is used to dissect the formulation of the first problem regarding the basis for implementing the rejang sang hyang iinan dance in the Pujungan Traditional Village. 2) Structural functional theory is used to dissect the formulation of the second problem regarding the process of implementing the rejang sang hyang iinan dance in the Pujungan Traditional Village. 3) The Theory of Meaning is used to dissect the formulation of the third problem regarding the meaning and function of the rejang sang hyang iinan dance in the Pujungan Traditional Village. The results of the research and data analysis show: (1) The basis for the implementation of the Rejang sang hyang iinan dance is seen from the perspective of a historical basis, a religious basis. The process of performing the Rejang sang hyang iinan dance is carried out at the pujawali kapat in Pujungan Village using facilities in the form of the sang hyang iinan. (2) The function of the sang hyang iinan rejang dance can be seen in terms of religious function, social function and cultural preservation function. (3) The philosophical meaning contained in the sang hyang iinan rejang dance is the aesthetic meaning, the meaning of Hindu religious education, and the ethical meaning.